Analisis Pemikiran Syekh Yusuf Al-Qardhawi Peran Zakat Penghasilan dalam Mengurangi Ketimpangan Sosial dan Ekonomi - Tegar Faiz Fahrezy; Nagita Aulia; Kanaya Audy; Lina Marlina (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the thoughts of Sheikh Yusuf Al-Qardhawi regarding income zakat and its role in reducing social and economic inequality. Income zakat is one of the instruments in the Islamic economic system that is believed to have significant potential in creating social justice. Sheikh Yusuf Al-Qardhawi, as one of the leading contemporary scholars, emphasized that income zakat must be optimized in a modern context as a form of social solidarity and redistribution of wealth. Through a descriptive qualitative approach, this study examines Al-Qardhawi's thoughts as expressed in his various writings, especially regarding zakat fiqh. The results of the analysis show that income zakat can be an effective tool in narrowing the economic gap between the rich and the poor, provided that its management and distribution are carried out professionally and transparently. In addition, Al-Qardhawi's thoughts emphasize the importance of the role of the state and zakat institutions in implementing income zakat widely and fairly. This study concludes that the concept of income zakat developed by Al-Qardhawi is relevant to be applied in the context of the contemporary economy to overcome the increasing social and economic inequality.